2023
DOI: 10.1186/s41235-023-00463-4
|View full text |Cite
|
Sign up to set email alerts
|

Expensive seems better: The price of a non-effective drug modulates its perceived efficacy

Abstract: Previous studies have shown that the price of a given product impacts the perceived quality of such product. This finding was also observed in medical contexts, showing that expensive drugs increase the placebo effect compared to inexpensive ones. However, addressing a drug's efficacy requires making causal inferences between the drug and the healing. These inferences rely on the contingency between these two events, a factor that is difficult to control in the placebo research. The present study aimed to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…Moreover, the price image also affected the purchase intentions of consumers [63]. Consumers believe that expensive medicines are more effective than low-cost medicines [64]. Consumers who purchase products at pharmacies tend to perceive low-priced products as untrustworthy [65], particularly in the case of herbal products.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the price image also affected the purchase intentions of consumers [63]. Consumers believe that expensive medicines are more effective than low-cost medicines [64]. Consumers who purchase products at pharmacies tend to perceive low-priced products as untrustworthy [65], particularly in the case of herbal products.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that multiple studies have indicated that higher-priced drugs are often associated with higher efficacy judgment. 25 Clearly, new antibiotics have been developed to target more resistant strains of bacteria. Nevertheless, this does not imply that the older antibiotics are any less effective than the new ones against the original strains of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Por ejemplo, se ha documentado que, si se consume un medicamento después de observar algún anuncio que lo publicite, se potencia la respuesta fisiológica para la que fue diseñado (Kamenica et al, 2013). Dado que elementos como el precio, disponibilidad y presentación del fármaco se asocian con su mejor calidad, no sorprende que un placebo costoso, visibilizado y elegantemente empacado genere una mayor respuesta terapéutica (Díaz-Lago et al, 2023). La industria farmacéutica se vale de esta mercadotecnia para argumentar que los medicamentos de patente son más efectivos, pero bien se podría tratar del efecto placebo inducido por la publicidad, el precio y la experiencia de desempacar el producto.…”
Section: Los Hongos (Ndi XI Tjo)unclassified